Student’s Perception of Brawl - Mutya Dwi Persimala; Daharnis Daharnis (Universitas Negeri Padang, 2023)
Brawls are behaviors that deviate from various norms. This study aims to describe students' perceptions of brawls with several aspects: (1) cognition, (2) affection, and (3) conation. This study uses a quantitative descriptive method. The population in the study were students of class X, XI, and XII at SMK Kartika I-1 Padang, totaling 172 students and the sample in this study amounted to 172 students. The sample was drawn using a saturated sampling technique. The instrument used in this study was a questionnaire with a Likert scale model. Data was processed using descriptive statistical analysis techniques. The research findings show that: students' perceptions of brawls seen from aspects of (1) cognition are in the good category, (2) affection is in the good category, (3) conation is in the good category. This means that students perceive that brawls are not good, can harm themselves and others, and are negative.